Quality and customer service, variables that affect compliance with luxury standards in international chain hotels in Bogotá, Colombia. - Zurbarán Arias, Deiwi Jesús (2023)
Luxury in the hotel has been practically since its inception, it is evident in its different goods and services, however, over time it has evolved and it has become more in demand, which has required innovation and creativity to meet the desires of customers. This article presents a documentary and descriptive review through an analysis of information from primary and secondary sources on the variables that affect compliance with luxury standards in terms of quality of service in hotels for international locks located in the city of Bogotá. , Colombia. The purpose of which was to analyze its impact on the operations of these organizations that provide luxury services in the country. It serves as a reference to consult on critical points, collecting experiences and knowledge contributing to the hotel sector in different parts of the world.